Losing Years of Human Life in Heavy Polluted Cities in Macedonia - Mirjana Dimovska; Mladenovska, Renata (ID Design/Scientific Foundation SPIROSKI, 2019)
INTRODUCTION: The urban air pollution will deteriorate globally, by 2050 outdoor particulate air pollution and ground-level ozone is projected to become the top cause of environmentally related deaths worldwide. AIM: To assess the burden of diseases due to particulate air pollution and health benefits form the pollution reduction policies. METHODS: Environmental burden of disease methodology has been applied. Environmental data for population exposure, total years of life lost from all causes, and relevant concentration-response functions have been used in estimation. RESULTS: The estimated disease burden from all causes (excl. external) is 30,256 YLL (19,436-40,625 95% CI) in Skopje Region, and 10,343 YLL (6,224-14,785 95% CI) in Tetovo. In terms of cardiopulmonary mortality, the estimated disease burden is 9,282/100,000 in Tetovo, in the Skopje Region 3,784/100,000 respectively. Annually in Tetovo 1,645 years of healthy life are lost, while in the Skopje Region 3,936 due to lung cancer premature mortality. The estimated health gain is significant, for the three selected health outcomes if EU limit values are reached, 41-42% of the estimated burden in Skopje Region will be eliminated, and 74-77% in Tetovo. CONCLUSION: the estimated impact of particulate air pollution on mortality is significant and not negligible. The same applies to the health and well-being of the population if the EU or WHO limit levels are reached.
Keywords: Environmental burden of disease; Health Gain; Particulate air pollution; Years of Life Lost